The Role of Euphemisms in Daily Communication:: A Contrastive Study of Palembang and Minangkabau Languages - Habib, Ikhwanul; Rahmadewi, Sintya (Jurnal Pendidikan Nusantara, 2025)
Euphemisms are an important part of the Indonesian language tradition, including in big cities like Palembang and Padang. The term refers to the use of more subtle words or expressions to replace words that are considered rude, taboo, or impolite. This study aims to examine the use of euphemisms in daily conversations in the two cities, each of which has different language features and cultural influences. This research uses a qualitative approach with a descriptive method. Data collection techniques used interviews and observations. The data sources came from the observations of researchers and native speakers of Palembang and Minangkabau languages. Data analysis uses data reduction, data explanation and concluding. Data validity uses triangulation. The results showed that the use of euphemisms in these two cities is different, based on the theory put forward by Allan and Burridge. In the Minangkabau language, there are nine forms of euphemisms, while in the Palembang language, there are thirteen forms. Both languages reflect the way people maintain social harmony and show respect for others through polite and subtle language. This research is expected to provide a deeper understanding of the role of language in maintaining politeness values in Palembang and Padang communities.